Immediate effects of sports taping applied on the lead knee of low- and high-handicapped golfers during golf swing - Kim, T. -G.; Kim, E. -K.; Park, J. -C. (The Journal of Strength and Conditioning Research, 2017)
Elite golf athletes suffer from various musculoskeletal injuries due to repeated golf swings. Repetitive varus moment during golf swing has been suggested as a possible cause of injuries to the lead knee. The aim of this study was to objectively and quantitatively evaluate the immediate effects of sports taping on the lead knee of elite golfers to restrict varus moment. Thirty-one elite golfers were assigned to the low- (LHG, n = 15) or high-handicapped group (HHG, n = 16). Using 3-dimensional motion analysis, the lead knee position on the frontal plane with and without rigid taping (RT), elastic taping (ET), and placebo taping was identified in 4 separate phases by the 5 events of golf swing as follows: the peak of the backswing (E1), parallel to the ground during downswing (E2), ball impact (E3), parallel to the ground during follow-through (E4), and finish (E5). The LHG when using a driver club had decreased movement toward knee varus with RT and ET than that without it from E1 to E2 (p = 0.001). The LHG when using a 5-iron club decreased movement toward knee varus with RT than that without it from E1 to E2 (p = 0.006) and from E2 to E3 (p = 0.019). The HHG when using a driver club had decreased movement toward knee varus with RT from E1 to E2 (p = 0.014). Sports taping may be helpful for elite golfers in terms of reducing varus moment of the lead knee during the downswing and be useful for the development of preventive strategies for golf-related knee injuries.